ASSESSMENT OF AVAILABILITY OF WOOD RESOURCES USING GEOGRAPHIC INFORMATION AND ANALYTICAL SYSTEMS (THE KRASNOYARSK TERRITORY AS A CASE STUDY) - Mokhirev, Aleksandr Petrovich; Pozdnyakova, Marija Olegovna; Medvedev, Sergej Olegovich; Mammatov, Vladimir Olimbaevich (Journal of Applied Engineering Science, 2018)
The article analyzes the availability of wood resources as a key indicator of the sustainability of logging operations.This study leads to the conclusion that the process of assessing the availability of wood resources is associated withthe collection and analysis of a large amount of data. At the same time, the more raw data is analyzed, the better theevaluation is. This article describes the experience of creating a software product based on geographic informationand analytical systems designed for detailed assessment of the entire set of factors that determine the level of availabilityof forest resources. The results of the assessment of the availability of wood resources in the KrasnoyarskTerritory are presented. The results obtained will allow to increase the effi ciency of the use of forest resources, toselect the ideal technology and system of machines, to avoid environmental disturbance, to develop the optimal routefor timber transportation which will eventually allow the forest user to make the largest profi t from the timber productsreceived.
Keywords: Profitability; Transport availability of wood resource; Geographical information and analytical systems; Logging; Availability of wood resources